Case Report: Refractory hypokalemia as a clinical manifestation of Crooke’s cell adenoma - Laura Kattah; Laura Kattah; Lizeth Bustamante; Daniela Sanabria; Daniela Sanabria; Johana Salazar (Frontiers in Medicine)
Crooke cell adenomas (CCA) are a rare and aggressive subtype of corticotrope tumors, with a prevalence of less than 1% pituitary adenomas, commonly manifest as Cushing’s syndrome. We present the case of a 62-year-old male with progressive lower limb oedema, hypertension, and severe refractory hypokalemia. In this case, severe hypercortisolism was identified with the presence of a pituitary microadenoma of 9×6 mm and adrenal bilateral hyperplasia. Ectopic hypercortisolism was discarded after further evaluation. The patient was taken to a transsphenoidal endoscopic resection with complete resolution of symptoms. Histopathological and microscopic studies revealed findings consistent with Crooke cells compatible with Crooke cell adenoma. This tumor subtype exhibits a heterogeneous clinical presentation and is infrequently reported in the literature. Consequently, it represents an unpredictable clinical entity with a variable medical course.